Documentation of the Kaisha-Database - The annual accounts database of Japanese stock companies 1970-1999. With a detailed glossary of Japanese accounting terminology - Horst Albach; Ulrike Görtzen; Tobias Miarka; Andreas Moerke; Thomas Westphal; Rita Zobel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This documentation provides an overview of the Kaisha Database, a database consisting of annual accounts data of Japanese manufacturing firms. The documentation is aimed at enabling the researcher interested in the database to work independently. The structure as well as the procedures used to create time series and to take account of the reforms in the accounting system are described. The excursuses give information on the Japanese accounting system and several data sources. In the appendix all firms are listed according to their security as well as industry code. Furthermore, all primary variables are presented in three languages (German, English, Japanese), and the calculation formulae of the workfiles are given. – – Die Dokumentation liefert einen Überblick über die .Kaisha-Datenbank., eine aus Jahresabschlüssen japanischer Industrieaktiengesellschaften erstellte Datenbank. Diese Dokumentation soll dazu dienen, Forschern das selbständige Arbeiten mit der Datenbank zu ermöglichen. Es werden die Struktur der Datenbank und auch das Vorgehen zur Erstellung von Zeitreihen und zur Einbeziehung der Reformen des Rechnungswesens beschrieben. Exkurse geben weitere detaillierte Informationen über das japanische Rechnungswesen und verschiedene Datenquellen. Im Anhang finden sich alle erfaßten Unternehmen mit ihrem Wertpapiercode und ihrer Industriezugehörigkeit. Desweiteren sind alle erfaßten Variablen in den Sprachen Deutsch, Englisch und Japanisch sowie die Berechnungsformeln der Workfiles angegeben.
Keywords: 330